Transfer scattering matrix of non-uniform surface acoustic wave transducers - N. C. Debnath; T. Roy (International Journal of Mathematics and Mathematical Sciences)
This paper is concerned with a general mathematical theory for finding the admittance matrix of a three-port non-uniform surface acoustic wave (SAW) network characterized by n unequal hybrid sections. The SAW interdigital transducer and its various circuit model representations are presented in some detail. The Transfer scattering matrix of a transducer consisting of N non-uniform sections modeled through the hybrid equivalent circuit is discussed. General expression of the scattering matrix elements for a N-section SAW network is included. Based upon hybrid equivalent circuit model of one electrode section, explicit formulas for the scattering and transfer scattering matrices of a SAW transducer are obtained. Expressions of the transfer scattering matrix elements for the N-section crossed-field and in-line model of SAW transducers are also derived as special cases. The matrix elements are computed in terms of complex frequency and thus allow for transient response determinations. It is shown that the general forms presented here for the matrix elements are suitable for the computer aided design of SAW transducers.